Pengukuran Waktu Kerja Karyawan Bengkel Hardchrome CV. Abad 21 Samarinda - Jonathan, Robin (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2008)
The research objective was to determine the time of labor standards hardchrome coating at the CV. Abad 21 in Samarinda. Research carried out for 2 months at the CV. Abad 21 in Samarinda with the object of research islimited regarding the calculation of working time for coating hardchrome workmanship. Data collected in the study include: an overview of hardchrome business, primary and secondaryobservational data, and the amount of labor. Data collection techniques used were: (1) observation, (2) interview, (3) documentation, and (4) the study of literature, namely the collection of data fromreports or records owned by CV. Abad 21 in Samarinda. The results indicated that: (1) the average time hardchrome coating at the CV. Abad 21 in Samarindaduring 5 times of observation is 501 minutes or 8 hours 21 minutes (2) the normal time hardchromecoating at the CV. Abad 21 in Samarinda is 501 minutes or 8 hours 21 minutes; and (3) coatinghardchrome standard time at the CV. Abad 21 in Samarinda by using the leeway factor of 15% ofnormal time is 576 hours or 9 hours 36 minutes.